Optimizing Risk Management of Sustainable Mortgage Financing at Islamic Bank in Indonesia - Fahmi Ilham Fadjar (JEBMAFA: Journal of Economics, Business, Management, Accounting, Finance, and Administration, 2025)
The significant growth of sharia mortgage financing in Indonesia requires optimal risk management so that the sustainability and stability of sharia financial institutions can be maintained. This article examines risk management strategies in sustainable sharia mortgage financing by emphasizing the importance of systematic risk identification, measurement, monitoring, and control processes. The author identifies six main risk categories, namely financing risk, market risk, liquidity risk, operational risk, sharia compliance risk, and external risk. Through an analysis of the stages of risk management and additional strategies such as portfolio diversification, compliance with sharia principles, and the use of protection instruments, this article highlights the need for an integrated risk management approach that is in accordance with maqashid sharia. The results of this study are expected to provide theoretical and practical contributions in strengthening the sharia mortgage financing system that is adaptive, transparent, and long-term oriented.